Some factors contributing to the completion or non-completion of college education of high-achieving high school graduates - Yuzon, Liberty (Fabella) 1922- (s.n.], 1969)
The problem of the study is to identify factors associated with completion or non-completion of college education of high achieving high school graduates of Fabella College. Results of the study may bring to light information that is important to the school's public image, and insights relative to revisions in school administrative programs, not only in this particular school but also in other similar provincial high schools in the Philippines.